PENGUATAN MATA KULIAH METODOLOGI PENELITIAN SEBAGAI UPAYA PENINGKATAN KUALITAS PENELITIAN MAHASISWA - Trianingsih, Rima (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
The selection of appropriate research methods is very important in the process of research. Research that want to find the quantitative truth can use quantitative research methods, such as experimental, survey, and ex post facto design. Research that want to describe a phenomenon by using expressions or descriptions can use qualitative research methods, such as action research, phenomenology, and case study. Research that want to make a product can use research and development methods. Research that would like to get the data in the form of quantitative and qualitative at once in one study can use mixed methods research. Research methodology course is a course that substantially in the development of the quality of research students. Therefore, the learning on research methodology courses should emphasize on contextual learning.